Developing a protocol for neuroimaging to investigate brain ageing and dementia in collaboration with aboriginal Australian communities. (December 2021) - Lavrencic, Louise; Broe, Gerald A.; Daylight, Gail; Delbaere, Kim; Draper, Brian; Duma, Stephen; Fulham, Michael; Hill, Thi Yen; Lasschuit, Danielle; Piguet, Olivier; Poulos, Lauren; Rae, Caroline; et al.
Abstract: Background: Dementia rates in Aboriginal Australians are 3‐5 times higher than in the broader Australian population, and among the highest rates reported globally. Existing evidence suggests that dementia types are similar to those found in non‐Indigenous Australian populations. Neuroimaging, however, has not been previously available in any study of dementia in this population to support or inform clinical diagnoses. Method: This study extends our epidemiological work, and arose from extensive community consultation and engagement. This engagement included a pilot MRI study (n=14), community planning survey, and guidance from an Aboriginal and Torres Strait Islander Steering Committee. The neuroimaging sub‐study is a prospective, cross‐sectional non‐interventional study. Participants first complete a comprehensive interview and diagnostic assessment as part of the Koori Growing Old Well study. Consenting participants with cognitive decline (diagnosis of cognitive impairment or dementia; n=40) and age/sex‐matched healthy controls (n=40) aged 60+ will undergo MR, FDG PET‐CT and PiB PET‐CT scans. An additional n=120 participants >55 years will be recruited to an MR scan‐only condition. Result: Pilot work and consultation showed acceptability of neuroimaging with partnering Aboriginal communities, including 74% of planning survey participants (n=213) indicating that neuroimaging should be included in future dementia studies (Lavrencic et al., 2020, Int Psychogeriatr). Older Aboriginal people living in New South Wales, Australia are currently being recruited; n=20 have undergone PET‐CT and MR scans to date (expected study completion by 2023). Outcome analyses will compare cognitive decline and healthy control groups on a range of measures including amyloid burden, regional glucose metabolism, hippocampal atrophy/volume and vascular indices on MR. Associations between amyloid burden and vascular pathology will be examined for cases of possible/probable Alzheimer's disease. Correlations between MR measures and early life stress, adult adversity, cognitive function, and clinically diagnosed cognitive impairment will be investigated. Conclusion: Our study will, for the first time, investigate functional and anatomical neuroimaging in older Aboriginal Australians and inform dementia prevention, diagnosis and policy for Aboriginal Australians. It will also contribute to the wider literature on vascular risk in the pathogenesis of AD, with associated biomedical and social risk factors across the lifespan of Aboriginal Australians.